2022
DOI: 10.3389/fphar.2022.944392
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preoperative duloxetine use for postoperative analgesia following laparoscopic cholecystectomy: A randomized controlled trial

Abstract: Background: The pain pattern after laparoscopic cholecystectomy (LC) is complex and distinct from postoperative pain after other laparoscopic procedures, suggesting that procedure-specific optimal analgesic management plans should be proposed. Duloxetine, a non-opioid neuromodulator, has been widely used to manage pain with dual central and peripheral analgesic properties.Aims: To assess the effect of preoperative administration of duloxetine compared to placebo on postoperative pain control in patients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Details of the included studies are shown in the table of characteristics of eligible studies (Table 1). Patients of the enrolled trial underwent knee arthroplasty, 20,25,47,48 spinal surgeries, 21,26–28,33,37,46 modified radical mastectomies, 22,24,35 abdominal hysterectomies, 23,32,36,40 laparoscopic gynecological surgery and cholecystectomy, 29,31,34,41,43,44 hip surgery, 30,39 shoulder surgery, 46 open colectomies, 42 and abdominal cancer surgery 38 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the included studies are shown in the table of characteristics of eligible studies (Table 1). Patients of the enrolled trial underwent knee arthroplasty, 20,25,47,48 spinal surgeries, 21,26–28,33,37,46 modified radical mastectomies, 22,24,35 abdominal hysterectomies, 23,32,36,40 laparoscopic gynecological surgery and cholecystectomy, 29,31,34,41,43,44 hip surgery, 30,39 shoulder surgery, 46 open colectomies, 42 and abdominal cancer surgery 38 …”
Section: Resultsmentioning
confidence: 99%
“…The dose of duloxetine administered as an intervention was 60 mg in included studies. Duloxetine or placebo was given for 1 day just before the operation, 29,32,34–36,38,40,41,43,44 for two consecutive days around the day of surgery, 20,23,26–28,31,37,42,45 for 5–7 days, 24,30,33,46 for 2 weeks, 22,25,39,47,48 and 2 weeks before to 2 weeks after surgery 21…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15] Areas under the curve (AUC) of the VAS were calculated by plotting the individual VAS score as curves in which the x-axis represented measurement time points from baseline (4-hours intervals) to 48 hours after surgery, and the y-axis represented the VAS score. [16] The secondary endpoints included total doses of rescue parenteral analgesics administered during hospital stay period, length of stay after operation, incidence of CPSP and patient's quality of life (QoL). CPSP was defined as the newly developed pain at the surgical site or incisional wounds within 3 months after surgery, as other etiologies of pain were excluded.…”
Section: Study Endpoints and Measurementsmentioning
confidence: 99%